A case report of hemophagocytic lymphohistiocytosis (HLH) associated with sarcoidosis - Gurung, Naresh; Karthak, Ashish; Saraf, Awin; Shrestha, Sanjeet Krishna (Nepalese Respiratory Journal, 2024)
Hemophagocytic Lymphohistiocytosis (HLH) is a rapidly progressing, fatal disorder characterized by severe systemic hyperinflammation presenting with unremitting fever, organomegaly (hepatosplenomegaly), cytopenias, raised inflammatory markers, liver failure, neurological issues, coagulopathy, and multiorgan failure. It is classified as primary due to mutations inherent to the individual causing increased macrophage activation or due to underlying secondary causes ranging from infections, malignancies, metabolic disorders, or rarely, rheumatological disorders such as juvenile idiopathic arthritis, SLE, sarcoidosis, and so on. However, the association between sarcoidosis and HLH has been rarely reported in the literature, which can present with features of sepsis, making the diagnosis challenging and requiring high clinical suspicion. We report the case of a patient with sarcoidosis presenting with recurrent fever, bilateral lower limb swelling, and fatigue, eventually developing fatal HLH that was unresponsive to high-dose steroids.